2012
DOI: 10.1645/ge-2966.1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Coccidial Infection in Dairy Cattle in Shanghai, China

Abstract: The prevalence of coccidial infections in dairy cattle was examined in Shanghai from November 2010 to March 2011. In total, 626 fecal samples from 24 dairy farms were examined; oocysts were identified to the species level based on morphological features. All herds were infected with Eimeria species. The overall prevalence of coccidia was 47.1%, with the highest prevalence in <4-mo-old calves (51.8%) and the lowest in >12-mo-old cattle (27.0%). The number of oocysts per gram of feces was significantly higher in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
20
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 13 publications
11
20
2
3
Order By: Relevance
“…In this study, there was a 6-fold increase in Eimeria spp. infection in ≤ 1 year animals (14.7%, Table 1) compared to >1 year old animals (2.7%); this is consistent with the data of other researchers reporting a strong correlation (P < 0.05) between age groups and infection (Chibunda et al 1997;Abebe et al 2008;Nalbantoglu et al 2008;Almeida et al 2011;Yu et al 2011;Dawid et al 2012;Dong et al 2012;NisarKhan et al 2013). All these results run counter to the study of Abebe et al (2008) who reported that risk of infection by Eimeria species appeared to increase with the age of the examined calves.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this study, there was a 6-fold increase in Eimeria spp. infection in ≤ 1 year animals (14.7%, Table 1) compared to >1 year old animals (2.7%); this is consistent with the data of other researchers reporting a strong correlation (P < 0.05) between age groups and infection (Chibunda et al 1997;Abebe et al 2008;Nalbantoglu et al 2008;Almeida et al 2011;Yu et al 2011;Dawid et al 2012;Dong et al 2012;NisarKhan et al 2013). All these results run counter to the study of Abebe et al (2008) who reported that risk of infection by Eimeria species appeared to increase with the age of the examined calves.…”
Section: Discussionsupporting
confidence: 86%
“…Research performed in other countries has revealed prevalence rates of Eimeria spp. varying from 17.9% to 93% in Poland (Pilarczyk et al 2000;Klockiewicz et al 2007;Pilarczyk et al 2009), 33% in Hungary (Farkas et al 2007), 22.6% and 33.3% in Brazil (Almeida et al 2011;Poscoti-Bruhn et al 2011), 35% to 47.1% in China (Yu et al 2011;Dong et al 2012), 50% in Pakistan (Nisar-Khan et al 2013), 22.7% and 68% in Ethiopia (Abebe et al 2008;Dawid et al 2012), 20%, 68% and 75% in Turkey (Arslan and Tuzer 1998;Cicek et al 2007;Nalbantoglu et al 2008), 29%, 50% and 52% in South Africa (Matjila and Penzhorn 2002), and 35% in Tanzania (Chibunda et al 1997). The rate was reported to be 21.3% and 18% to 50% in the Kurdistan and East-Azerbaijan provinces of Iran (Yakhchali and Gholami 2008;Yakhchali and Zarei 2008;Davoudi et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The adult animals generally suffer from sub-clinical form of disease and act as a source of infection to young and/or newly added stock. A variable prevalence rate of coccidiosis in adult dairy animals has been reported by several workers worldwide, including India (Muraleedharan 2005;Manya et al 2008;Yu et al 2011;Dong et al 2012;Gupta et al 2012;Laha et al 2013). Recent studies from Punjab state reported a prevalence rate of 3.77 % (Singh et al 2012a) and 0.95 % (Singh et al 2012b) from cattle and buffalo populations, respectively.…”
Section: Discussionmentioning
confidence: 93%
“…The prevalence of coccidiosis in cattle and buffaloes has been well reported from different parts of world (Yu et al 2011;Dong et al 2012) including India (Manya et al 2008;Laha et al 2013) but information regarding prevalence of coccidiosis in cattle and buffalo populations from Punjab state seems to be sporadic Jyoti et al 2011;Singh et al 2012a, b). Moreover, no attempt has been made to determine the species composition of coccidian infection in Punjab.…”
Section: Introductionmentioning
confidence: 98%
“…infection in ≤ 1 year animals (36.96%, Table 6) compared to >1 year old animals (11.66%). This general young bias in Eimeria infection is well documented in cattle throughout the world [9,18,36,[39][40][41]. Acquired immunity has been shown to cause a decrease in infection of various Eimeria species with host age [40,42].…”
Section: Locality Examined Number Infected Number Prevalence (%) Signmentioning
confidence: 99%